Stress, anxiety, and depression among junior high school students in Purwokerto, Indonesia - Agustina, Sindy; Elsanti, Devita (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Adolescence is a critical phase characterized by rapid physical, psychological, and intellectual development. Adolescents often exhibit a high level of curiosity, boldness, and impulsive behavior, which, if not properly directed, can lead to physical and mental health problems. The impact of mental health disorders in adolescence is far-reaching, affecting not only the current quality of life but also the future potential of individuals and society. Purpose: To determine the level stress, anxiety, and depression among junior high school students in Purwokerto, Indonesia, Method: Quantitative research with descriptive survey type to explore the mental health condition of adolescents with a focus on stress, anxiety, and depression levels. This study was conducted at Telkom Junior High School, Purwokerto. The sampling technique used was purposive sampling and a sample of 114 respondents was obtained according to the inclusion criteria that had been set, namely adolescents aged 11-13 years and in grade 7. Data collection was carried out using an online questionnaire adapted from a validated psychological scale, namely the Depression Anxiety Stress Scales (DASS) and the Kessler Psychological Distress Scale (K-10). Results: The majority of respondents' age data is 12 years old, as many as 83 respondents (72.8%) with an average value and standard deviation of 12.219 ± 0.475, in the age range of 11-13 years. Most respondents are male, as many as 70 respondents (61.4%). Most respondents experience moderate stress, as many as 52 respondents (45.6%), moderate anxiety, as many as 43 respondents (37.7%), and the normal category at the level of depression, as many as 83 respondents (72.8%). Conclusion: Emotional disorders, such as stress, anxiety, and depression are common among students. Sociodemographic factors, including age and gender significantly influence students' mental health. Male students are more susceptible to stress and anxiety, while female students are more susceptible to major depression due to more complex biological and psychological factors. Suggestion: Emotional disorders, such as stress, anxiety, and depression that occur in adolescents do need to be considered by various parties, especially parents who have more time with their children. In addition, schools must create a comfortable school environment and implement school-based mental health programs.